Principles of Modeling Students in Their Future Professional Activity From Simple to Complex, From Abstract to Accuracy (Eurasian Scientific Herald, 2022)
In this article, the theoretical basis of modeling students in their future professional activities is presented. also quot; in professional activity, the principles of modeling from simple to complex, from abstract to accuracy are theoretically based.